The Role of Brand Authenticity and Brand Oldness Association for Brand Love and the Impact on Relation Quality and Brand Consciousness - Mayasari, Iin; Hoo, Wong Che; Bahtar, Azlin Zanariah (Indian Journal of Marketing, 2025)
Purpose : This research analyzed brand love regarding authenticity and oldness association. It also explained the role of brand love in relationship quality and brand consciousness as a form of consumer behavior that remained loyal to the brand. Methodology : The research design was descriptive and quantitative, using surveys for data collection. Data analysis used a structural equation modeling approach via the PLS statistical tool. The respondents who completed the questionnaire selected the global classical brands in Indonesia that had survived amid the influence of global brands. Findings : This study significantly influenced branding, consumer psychology, and relationship marketing. It examined the relationship between brand authenticity and brand oldness association as predictors of brand love and the impact of brand love on brand consciousness and brand oldness association. Brand consciousness was a component of consumer psychology, whereas relationship quality was a component of relationship marketing. Practical Implications : Establishing a two-way communication channel facilitated the cultivation of an atmosphere of genuineness and enabled consumers to perceive brand authenticity. Originality/Value : The research model incorporated the concepts of brand authenticity and oldness, which explained the formation of brand love, especially for product brands that survived for a certain period. The impact of brand love on relationship quality and brand consciousness was also researched.